ECONOMIC PERFORMANCE PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dirvi Surya Abbas; Winda Ningsih; Susilawati Susilawati (Simposium Nasional Mulitidisiplin (SinaMu), 2020)
The purpose of this study was to determine the effect of company size, profitability and capital structure on economic performance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2015-2019 period. The population of this study includes all food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period. The sampling technique was using purposive sampling technique. Based on the predetermined criteria, 9 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The results show that company size has a positive and significant effect on economic performance, profitability has a positive but insignificant effect on economic performance, capital structure has a positive but insignificant effect on economic performance.